2020
DOI: 10.1088/1361-6501/abc0b1
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of hydrophones using a frequency domain filter processing method: theory and experiment

Abstract: To eliminate the interferences coming from the boundaries of a water tank and extend its low frequency calibration limit, a frequency domain filter processing (FDFP) method is proposed for hydrophone calibration measurements. The frequency domain filter function is designed according to the a priori spatial position of projector and hydrophone pair in a water tank. A simultaneous comparison method is used for calibration, and a wideband pink noise pulse signal is transmitted. After application of the FDFP meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Blake and Maga [5] were the first to demonstrate through experiments that a nonanechoic water tank satisfies the diffuse-field conditions in the frequency band above the Schroeder cutoff frequency; they also demonstrated that the diffusion field theory commonly used in a reverberation chamber in air is also applicable to a non-anechoic water tank. On the basis of their research work, after decades of development, non-anechoic tanks have been widely used in many fields, including the calibration of underwater transducers, [6][7][8] measurement of the acoustic parameters of underwater acoustic materials, [9,10] and measurement of the sound power radiated from complex structures. [11][12][13][14] The premise of using diffuse-field measurement methods in a non-anechoic water tank is that the modal density in the tank will be sufficiently high that the measurement of the reverberation time will have very good consistency.…”
Section: Introductionmentioning
confidence: 99%
“…Blake and Maga [5] were the first to demonstrate through experiments that a nonanechoic water tank satisfies the diffuse-field conditions in the frequency band above the Schroeder cutoff frequency; they also demonstrated that the diffusion field theory commonly used in a reverberation chamber in air is also applicable to a non-anechoic water tank. On the basis of their research work, after decades of development, non-anechoic tanks have been widely used in many fields, including the calibration of underwater transducers, [6][7][8] measurement of the acoustic parameters of underwater acoustic materials, [9,10] and measurement of the sound power radiated from complex structures. [11][12][13][14] The premise of using diffuse-field measurement methods in a non-anechoic water tank is that the modal density in the tank will be sufficiently high that the measurement of the reverberation time will have very good consistency.…”
Section: Introductionmentioning
confidence: 99%